Effect of Leucaena leucocephala (Lam.) de wit pruning frequency on alley cropped maize/cassava - Welke, S.E.; Tanyi, E.; Kang, B. (1995)
A study was undertaken to assess the effect of different pruning intervals of Leucaena leucocephala hedgerows on alley cropped maize and cassava. Farmers often delay hedgerow pruning in alley cropping systems due to labor, and financial constraints. It is not clear, however, when hedgerow shading becomes detrimental to crop growth. Crop growth and yield were measured in relation to available light and soil moisture under Leucaena hedgerows which were pruned every 2, 4, 6, 8 and 10 weeks. A control of unpruned hedgerows was included. Marked reductions in maize yield were recorded when hedgerow pruning was delayed beyond 10 weeks after crop planting; while cassava yield was not affected. A general trend of taller plants with thinner stems was observed when Leucaena hedgerows were not pruned or pruned at intervals of 8 weeks. Plants adjacent to hedgerows were usually shorter than those in the middle of the alleys. Yield decline and growth effects were attributed to shading, rather than soil moisture depletion by the hedgerows. This study demonstrated that hedgerow pruning can be delayed up to 10 weeks after planting maize without significant yield reduction. Further studies are necessary to determine optimum pruning intervals for a maize/cassava intercrop in an alley cropping system.